f′(x)=ex(x2-3x+1)+ex(2x-3)
=ex(x2-x-2),
令f′(x)=0得x2-x-2=0
f′(x)=x2-x+2=(x+1)(x-2).
列表如下:
x | (-∞,-1) | -1 | (-1,2) | 2 | (2,+∞) |
f′(x) | + | 0 | - | 0 | + |
f(x) | 單調(diào)遞增 | 極大值 | 單調(diào)遞減 | 極小值 | 單調(diào)遞增 |
(2)f′(x)=ex(x2+ax+1)+ex(2x+a)
=ex[x2+(a+2)x+(a+1)],
令f′(x)=0得x2+(a+2)x+(a+1)=(x+1)(x+a+1)=0,由于實(shí)數(shù)a滿足a≤-1,
所以f(x)的極小值點(diǎn)x=-(a+1),則g(x)的極小值點(diǎn)也為x=-(a+1),
而g(x)=2x3+3(b+1)x2+6bx+6,g′(x)=6x2+6(b+1)x+6b=6(x+1)(x+b),
所以a+1=b,
即b=a+1.
又因?yàn)閍≤-1,∴b≤0
所以g(x)極大值=g(-1)=-2+3(b+1)-6b+6=-3b+7≥7.
故g(x)的極大值大于等于7.